Acute kidney injury in hospitalized patients with COVID-19 (retrospective study) - Azeem, Haitham A. (Egypt J Bronchol, 2021)
BACKGROUND: The World Health Organization (WHO) has named the virus as 2019 novel coronavirus on January 12, 2020, and has declared a public health emergency globally on January 30, 2020. The epidemic started in Wuhan, China, in December of 2019 and quickly spread to over 200 countries. COVID-19 can cause multiple organ injuries (e.g., kidney, heart, blood, and nervous system). Among them, acute kidney injury (AKI) is a critical complication due to its high incidence and mortality rate. So, it is essential to evaluate AKI in COVID-19 patients during this pandemic state. The aim of this work is to detect the occurrence of AKI in hospitalized COVID-19 patients. So, a retrospective study was conducted on hospitalized adult patients > 18 years old with confirmed SARS-CoV-2 infection admitted to the Abo Teeg Hospital at Assiut City, Egypt, from May 1, 2020, to July 1, 2020. All data were collected from medical records, patients’ follow-up, and charts. Data were verified, coded by the researcher, and analyzed using IBM-SPSS 21.0. RESULTS: Eighty-six COVID-19 patients were admitted to Abo Teeg Hospital in Assiut City, Egypt, between May and July 2020. Thirty-eight patients (33%) were of the male gender. Mean age was 58.07 ± 17.9, and 61 patients developed AKI. 32.8% of the AKI group were a stage I severity (increase in serum creatinine by 0.3 mg/dl within 48 h), 21.3% of them presented by stage II (2–2.9 times increase in serum creatinine), and 45.9% were in stage III (3 times or more increase in serum creatinine). The overall hospital mortality for the patients admitted to ICU with AKI was 6.7% (11/61), compared to 1% (4/25) in those without AKI. CONCLUSION: Hospitalized patients with COVID-19 had a higher risk of AKI, and we recommended that those patients should be evaluated after discharge for the development of CKD.